ChemInform Abstract: Divergent Total Synthesis of Indoxamycins A, C, and F. Issue 21 (27th May 2014) - He, Chi; Zhu, Chenlong; Dai, Zhifeng; Tseng, Chih‐Chung; Ding, Hanfeng
Abstract Based on the total syntheses the originally reported structures of the target compounds are revised.